Opioid analgesics in experimental sepsis: effects on physiological, biochemical, and haemodynamic parameters. (5th April 2012) - Nardi, Geisson Marcos; Bet, Angela Cristina; Sordi, Regina; Fernandes, Daniel; Assreuy, Jamil
Abstract Cecal ligation and puncture (CLP) is the sepsis model that more closely resembles the human pathology, but it is likely to cause suffering to experimental animals. However, it is not clear whether the use of analgesia may affect some parameters evaluated in experimental sepsis research. Therefore, we investigated the effects of fentanyl and tramadol in experimental sepsis in the rat. The following parameters were evaluated: body temperature, body weight, water and food ingestion, mortality, analgesia, blood leukocytes, mean arterial blood pressure, vascular reactivity to phenylephrine, lung myeloperoxidase activity, and plasma levels of IL1‐β, glutamic‐oxaloacetic, glutamic‐pyruvic, lactate, creatinine and urea. While producing significant analgesia, the opioids modify minimally the parameters, with the exception of sepsis‐induced hypotension and mortality. Although fentanyl and tramadol can minimize pain and the general suffering of animals submitted to CLP surgery, their effects on cardiovascular parameters as well as in the mortality indicate that their use in experimental sepsis must be done with caution and with all the proper control groups.